Money Diver - W., F. (My University, 2010)
A group of young men watch as one of their members takes a dive into the sea.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Boats and boating--Trinidad and Tobago; Divers--Trinidad and Tobago; Skin diving--Trinidad and Tobago; Young men--Trinidad and Tobago